Efeito da inclusão de raspa integral de mandioca e formas de arraçoamento sobre o desempenho de leitões na fase inicial - Oliveira, Tânia Elizabeth Sampaio (2005)
32 piglets were used to castrate commercial line weaned at 21 days of age with approximately 6.0 kilograms of weight, to evaluate the effects of different levels (0, 12, 24 and 36%) of full inclusion of scraping of cassava (RIM) and forms of arraçoamento on the performance of breeding pigs in the initial stage - I (21 to 42 days of age), the initial phase - II (42 to 70 days old) and total phase (21 to 70 days of age), and its economic viability. The diets were isoproteic (21.0 and 19.0%) and isocaloric (3,100 and 3,200 kcalEM / kg), respectively. The experimental design was a block at random in a 4 x 2 factorial (four levels of inclusion of RIM) and two forms of arraçoamento (dry and wet diets), with four repetitions per eatment and one animal per share. The criterion for training block was the initial weight of piglets. The gain in average daily weight (GPMD), the average daily consumption of feed (CRMD), and feed conversion (CA) did not differ significantly (P> 0.05) for different levels of between RIM and the forms of arraçoamento. It follows that it is technically feasible to use the full scraping of cassava to the level of 36% in pig feed in the initial phase (21 to 70 days of age), regardless of the form of arraçoamento and that the level of inclusion of 12% RIM, which was the best response showed bioeconômica.